Pregnancy outcome in bicornuate uterus with pre-term labor: a case report - Saikia, Smriti Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Reproductive outcome and pregnancy rates are relatively challenging in women with uterine anomalies. Pregnancies in bicornuate uterus are considered as high-risk pregnancies which requires adequate antenatal screening and early diagnosis to prevent complications. Many cases remain asymptomatic but in later age during pregnancy it leads to severe complications.